STUDENTS’ DIFFICULTIES IN MAKING INFERENCE IN READING NARRATIVE PASSAGES AT THE SOCIAL ELEVENT GRADE OF SMAN 1 CURUP - Nining Warnidah; Bambang Suwarno; Arono . (Universitas Bengkulu, 2016)
This study aimed to find out the students’ difficulties in making inference in reading narrative passages in making inference in reading narrative passages. The population of this study included the eleventh graders of SMAN 1 Curup, and the students of XI SOS 4, which consisted of 34 students, became the research sample. For the instrument, the researcher used reading test which consisted of 40 questions and questionnaire which consisted of 30 items. The result showed that the students’ overall difficulty in making inference in reading narrative passages belonged to “moderate” category. It was proved by the students’ reading error mean score which was 47.5. The students’ highest difficulty was on inferences about the author’s attitude (5.88%, or “very high”).